Progesterone Levels and Reproductive Parameters in the Periovulatory Period of Nellore Cows under FTAI protocol - Sousa, Aldo Barbosa; Menezes, Artur Azevedo; Batista, Lucas Andrê Silva; Loiola, Marcus Vinicius Galvão; Bittencourt, Rodrigo Freitas; Filho, Antônio de Lisboa Ribeiro; Rodrigues, Alexandra Soares (Acta Scientiae Veterinariae, 2022)
Background: Fixed Time Artificial Insemination (FTAI) has achieved a significant evolution in the last 18 years, however, despite the progress achieved by modern FTAI programs, the conception rates obtained are still low. Therefore, this study aimed to evaluate the interrelation between progesterone levels in the periovulatory period and reproductive parameters of Nellore cows submitted to an FTAI protocol. Materials, Methods & Results: On a random day, called day 0 (D0), 57 cows received a P4 device associated with the intramuscular (IM) application of 2.0 mg of estradiol benzoate. On D9, the P4 devices were removed and then were administered 500 μg of cloprostenol sodium IM; 0.6 mg of estradiol cypionate IM and 300 IUI of Equine Chorionic Gonadotrophin IM. Blood samples were collected for the determination of serum P4 concentrations on D9 and D11 of the protocol. The evaluations of follicular diameter (DFOL), follicular wall area (AFOL) and the vascularization area of the follicle wall (VFOL) were carried out on D11 using B-mode ultrasonography examination and colour Doppler, and then the artificial inseminations were performed. The evaluation of the corpus luteum diameter (CLD), of the total corpus luteum area (CLA), of the area of corpus luteum vascularization (CLV) and blood sampling for determination of post-ovulatory P4 levels (Post-P4) were performed on D24. For the analysis of the P4 concentration the chemiluminescence method was used, with a sensitivity of 0.1 ng/mL. According to the P4 concentrations on D11, cows were divided into 2 groups, LOW LEVELS OF P4 and HIGH LEVELS OF P4. The diagnosis of pregnancy was performed using transrectal ultrasonography on D45, at this point the cows were divided into 2 groups, PREGNANT and NON-PREGNANT. The correlation between DFOL and P4 dosage on D11 was moderate, negative and significant and between the AFOL and the serum P4 levels on D9, was moderate, negative and significant. As for the other correlations between follicular and luteal parameters and serum P4 levels, these were low to moderate, negative and not significant. Cows in the LOW LEVELS OF P4 group had significantly larger diameter and follicular areas than the cows in the HIGH LEVELS OF P4 group, the other follicular and luteal parameters showed no statistical difference. Of the total 57 cows that were inseminated, 30 cows became pregnant. Cows in the PREGNANT group had serum P4 levels on D9 equivalent to that obtained by the NON-PREGNANT group. However, at D11 the cows that became pregnant presented significantly lower serum P4 levels than cows that did not become pregnant. Discussion: The results of the interrelation between follicular parameters and P4 levels obtained in the present study, pointed out that the lower the levels of P4, the higher the follicular parameters, corroborating with other authors. Thus, larger preovulatory follicles provided high ovulation rates. Periovulatory serum P4 levels did not significantly affect the morphofunctional parameters of the CL. Such findings may be justified by high periovulatory P4 levels resulting from less efficient luteolysis, exert a negative effect on the results of FTAI protocols, because progesterone inhibits the release of LH pulses. It is concluded that lower periovulatory P4 levels established a favourable condition for follicular development and fertility, however, morphofunctional parameters of the corpus luteum were not affected. Keywords: follicular development, fertility, conception rate, ovarian hemodynamics, synchronization. Título: Níveis de progesterona e os parâmetros reprodutivos no período periovulatório de vacas Nelore submetidas ao protocolo de IATF. Descritores: crescimento folicular, fertilidade, índice de concepção, hemodinâmica ovariana, sincronização.